Stronger Prejudices Are Associated With Decreased Model-Based Control - Sebold, Miriam; Chen, Hao; Önal, Aleyna; Kuitunen-Paul, Sören; Mojtahedzadeh, Negin; Garbusow, Maria; Nebe, Stephan; Wittchen, Hans-Ulrich; Huys, Quentin J. M.; Schlagenhauf, Florian; Rapp, Michael A.; Smolka, Michael N.; et al. (Frontiers in Psychology, 2022)
Prejudices against minorities can be understood as habitually negative evaluations that are kept in spite of evidence to the contrary. Therefore, individuals with strong prejudices might be dominated by habitual or “automatic” reactions at the expense of more controlled reactions. Computational theories suggest individual differences in the balance between habitual/model-free and deliberative/model-based decision-making. 127 subjects performed the two Step task and completed the blatant and subtle prejudice scale. By using analyses of choices and reaction times in combination with computational modeling, subjects with stronger blatant prejudices showed a shift away from model-based control. There was no association between these decision-making signatures and subtle prejudices. These results support the idea that blatant prejudices towards minorities are related to a relative dominance of habitual decision-making. This finding has important implications for developing interventions that target to change prejudices across societies.